SISTEMPEMBELAJARAN TERPADU DI SEKOLAH - Hasnawati Hasnawati (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
Integrated learning is an approach to learning that links several aspects of both the intra-subject and between subjects. With the approach of the students will acquire knowledge and skills in their entirety so that learning becomes meaningful to students. Provide meaningful learning in integrated learning means that studentswill be able to understand the concepts they learned through direct experience and concrete links between the concept of intra-subject and between subjects. Integrated learning as a concept is an approach to learning that involves some subjects to providemeaningful learning experiences for children. Integrated learning approach that is believed to be as practice-oriented learning in accordance with the needs of today’s children. With integrated learning students are expected to have the ability to identify, collect, assess and use information around them significantly.